The Effect of the Scientific Approach with Comic Intelligent Media Support on Students’ Science Competencies - Nandang Hidayat; Teti Rostikawati (STKIP Singkawang, 2018)
This study aims to test the effectiveness of the use of intelligent comic media combined with the process of learning with scientific approach onstudents’ science competence. The research method used is quasi experimental method with 2x2 factorial design. The study involved four teachers and 112 students of grade 4 from SDN Pertiwi, SDN Polisi 1, SDN Kebon Pedes 1, and SDN Kebon Pedes 5 in Bogor city. The study was conducted in the first half of the academic year 2014/2015. This study concludes that the use of intelligent comics combinedunitedly in the learning process with scientific approach significantly influence the science competence of grade 4 elementary school students on the aspects of knowledge and scientific attitude, but does not significantly affect the competence of science for the aspects of science process skills. This study also concludes that there is no interaction between the learning process as the treatment variable and the involvement of the students in the out-of-school learning guidance (tutorial) as the moderator variable. That is, the influence of the learning process on the students’competence of science on aspects of knowledge and scientific attitudes are not contaminated by the involvement of the students in the guidance of learning.